1989
DOI: 10.1210/mend-3-1-185
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid and Cyclic Nucleotide Regulation of Plasminogen Activator and Plasminogen Activator-Inhibitor Gene Expression in Primary Cultures of Rat Hepatocytes

Abstract: Primary cultures of rat hepatocytes produce tissue-type plasminogen activator (tPA) and plasminogen activator-inhibitor type 1 (PAI-1). Incubation of hepatocytes with 50 microM 8-(4-chlorophenylthio)cAMP (CPT-cAMP) results in a 4-fold increase in tPA activity, whereas the synthetic glucocorticoid dexamethasone (1 microM) causes a more than 90% decrease. In combination, dexamethasone completely overcomes the CPT-cAMP effect and markedly decreases PA activity. PAI-1 is induced by both CPT-cAMP and dexamethasone,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 73 publications
(33 citation statements)
references
References 58 publications
2
30
0
1
Order By: Relevance
“…Many different cell types and tissues express tPA at variable levels, and often the expression is regulated by hormones and growth factors (23,46,53,62). In unstimulated rat granulosa cells, the level of tPA mRNA is low, but following FSH stimulation, the level is rapidly increased about 20-fold, after which there is a slow decrease to the level found in untreated cells (43,45).…”
Section: Resultsmentioning
confidence: 99%
“…Many different cell types and tissues express tPA at variable levels, and often the expression is regulated by hormones and growth factors (23,46,53,62). In unstimulated rat granulosa cells, the level of tPA mRNA is low, but following FSH stimulation, the level is rapidly increased about 20-fold, after which there is a slow decrease to the level found in untreated cells (43,45).…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistically, corticosteroids can decrease serum levels of cytokines that cause reactive inflammation and hypercoagulability in the immediate postoperative period [11,12,14,26]. However, corticosteroids also can increase the synthesis and release of clotting factors and fibrinolysis inhibitors, thereby enhancing coagulation [9,10,18]. Therefore, further study is indicated to explore the topic of thromboembolic events in chronic corticosteroid users.…”
Section: Discussionmentioning
confidence: 99%
“…PAI-1, as a member of the SERPIN (Serine Protease Inhibitor) family, is a single chain, 50-kDa glycoprotein that can be produced by platelets, vascular endothelial cells, vascular smooth muscle cells, and some other nonvascular cell types such as hepatocytes. [1][2][3] Moreover, a factor known as protein C inhibitor (PCI), which can be synthesized in liver and some other steroidresponsive organs, was proposed to be named PAI-3. 4 We and others have shown that PAI-1 gene expression can be induced by hypoxia via binding of the transcription factor hypoxiainducible factor-1 (HIF-1) to hypoxia response elements (HREs) in the PAI-1 gene promoter.…”
Section: Introductionmentioning
confidence: 99%